The "True King's Queen": Unlocking the Performance Potential of the Queen in Shakespeare's Richard II. (3rd April 2022) - Higgins, Laura
ABSTRACT: Reviewing the Old Vic's 1947 production of Richard II, W. A. Darlington commented "Margaret Leighton does what can be done with a Queen to whom Shakespeare gives no name and history no place": an opinion endorsed by many reviewers across the twentieth century. More recently, however, theatre critics have identified hitherto unseen qualities in Richard II 's Queen, suggesting the need to reappraise her theatrical potential and recover her vitality and significance on the modern stage. Examining a selection of moments from contemporary performance, I present a gallery of contrasting faces that show the Queen is a prismatic figure of affective, political, and spiritual dimensions. By focusing on the contradictions that the Queen displays as she navigates the tensions inherent in balancing desires for personal fulfilment in affective relationships with social and political responsibilities and the need to survive in a volatile and male-dominated world, I avoid constructing her according to traditional gender binaries. I suggest that these contradictions render Richard II 's Queen meaningful for our contemporary moment which acknowledges ambiguities in the construction of identities and recognises the constructive possibilities of shifting between positions as a means of processing and judging complex issues.